Distribution of arbuscular mycorrhizal fungi (AMF) in Terceira and São Miguel Islands (Azores) - Melo Drumonde, Catarina (2020)
The data, presented here, come from samples collected during three research projects which aimed to assess the impact of land-use type on Arbuscular Mycorrhizal Fungi (AMF) diversity and community composition in pastures of Terceira Island (Azores, Macaronesia, Portugal) and also in the native forest of two Azorean Islands (Terceira and São Miguel; Azores, Macaronesia, Portugal). Both projects contributed to improving the knowledge of AMF community structure at both local and regional scales.